UNDERSTANDING PEER AND TEACHER ASSESSMENT ABOUT LABORATORY SKILL ON FORMATIVE ASSESSEMENT THROUGH SCIENTIFIC APPROACH - Arlianty, Widinda Normalia; Febriana, Beta Wulan (Proceedings of the International Conference on Education, 2017)
In order to obtain a holistic view of students’s contribution peer assessment used in addition to teacher assessment to arrive at overall course grade of a students in scientific approach. However, students based assessment to determines final value still lots raises questions. Although, literature shown student based assessment useful to review and evaluate the right skills in scientific approach, but assessment between students and teacher have different perceptions toward viewpoints in assessments. Therefore, the aim of this study was to identify differences and similiarities between peer assessment and teacher assessment. The samples of this research were 2nd-semester were following physical chemistry experiment in the laboratory. The research was quasi experimental. The scope of this study is limited to laboratory skill in the laboratory and that were assessed using peer and teacher assessment. The data peer and teacher assessment were collected by observation sheet in experiment. Students in each group were asked to give confidential assessment to review laboraty skill of their group. The data analysis result indicate that students tend to give similiar scores to peers, which are much higher than what were given by their teacher. In conclusion, that student based assessment does provide information on laboratory skill of peers which may not accordance with assessment is given by teacher. Understanding that contributes that was privided by students againts assessment learning process is important as basic a review of teachers help students be learners have good laboratory skill through scientific approach.